2003
DOI: 10.1111/j.1545-5300.2003.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Secrecy: A Comparative Study of Juvenile Sex Offenders and Youth with Conduct Disorders

Abstract: The reported research was designed to compare adjudicated male juvenile sexual offenders and youth with conduct disorders on five aspects of family secrecy and deception. Twenty-nine male juvenile sex offenders and 32 comparison youth from three child welfare agencies in New York State participated in the study. Research assistants, blind to the hypotheses of the study and status of the youth, coded agency records for five variables identified a priori as a basis of comparison. Analyses revealed that the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…One interesting question is whether families of sex offenders are more inclined to cover up the problem than are families of non-sex offenders. Baker, Tabacoff, Tornusciolo, and Eisenstadt (2003) found that families of sex offenders told more lies, had more family myths, and were more likely to be involved in taboo behavior. A consequence of this attitude may be that problems within the families of sex offenders are not well recognized, whereas these families may well be more disturbed than families of non-sex offenders.…”
Section: Inconsistent Resultsmentioning
confidence: 99%
“…One interesting question is whether families of sex offenders are more inclined to cover up the problem than are families of non-sex offenders. Baker, Tabacoff, Tornusciolo, and Eisenstadt (2003) found that families of sex offenders told more lies, had more family myths, and were more likely to be involved in taboo behavior. A consequence of this attitude may be that problems within the families of sex offenders are not well recognized, whereas these families may well be more disturbed than families of non-sex offenders.…”
Section: Inconsistent Resultsmentioning
confidence: 99%
“…Eight studies reported higher rates of child sexual abuse (CSA) victimization among adolescent sexual offenders (ASOs) than other offender groups (Burton et al, 2002;Milloy, 1994;Monto, Zgourides, & Harris, 1998;Truscott, 1993;Zakireh et al, 2008), nonoffenders (Monto, Zgourides, Wilson, Harris, 1994), adolescents with a diagnosis of oppositional defiant disorder (Moody, Brissie, & Kim, 1994), or adolescents in residential treatment (Bagley & Shewchuk-Dann, 1991). In contrast, eight studies found no differences between ASOs and other delinquent youth on history of sexual abuse (Awad & Saunders, 1991;Baker, Tabacoff, Tornusciolo, & Eisenstadt, 2003;Burton et al, 2002;Ford & Linney, 1995;Johnson-Reid & Way, 2001;Rubenstein, Yeager, Goodstein, & Lewis, 1993;Spaccarelli, Bowden, Coatsworth, & Kim, 1997;van Wijk et al, 2007). Notably, several studies of ASOs used mixed samples of offenders who perpetrated against children or their adolescent peers (e.g., Milloy, 1994;Moody et al, 1994;Zakireh et al, 2008).…”
Section: Relationship-level Factors Family Factors Family Environmentmentioning
confidence: 99%
“…Some professionals have argued that families should be amalgamated by any means necessary, and others have argued that youths may not benefit from familial involvement (Ryan, 2010a;Baker, Tabacoff, Tornusciolo, & Eisenstadt, 2003). The field has recently begun to discuss broad approaches and specific interventions aimed at incorporating families into the treatment process.…”
Section: Family-oriented Approaches and Evidencementioning
confidence: 98%